2011
DOI: 10.1111/j.1465-7287.2011.00281.x
|View full text |Cite
|
Sign up to set email alerts
|

Financial Development and Income in African Countries

Abstract: This paper presents an empirical analysis of the relationship between financial system development and economic development. Using cointegration and vector autoregressive estimations on annual data from Africa, we examine the nature of the relationship between financial development and income. We find mixed results on both the short‐ and the long‐run relationships between the two variables. We find finance causing income, income causing finance, and bidirectional causality. The results indicate that neither th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Finally, refs. [10,[47][48][49] found evidence of bidirectional causality and reverse causation. On the other hand, ref.…”
Section: Financial Development and Economic Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, refs. [10,[47][48][49] found evidence of bidirectional causality and reverse causation. On the other hand, ref.…”
Section: Financial Development and Economic Growthmentioning
confidence: 99%
“…Several cross-country regression analyses support the tight link be-tween credit access and economic growth [5,6], and this has been shown in developed and developing economies [7,8]. Recent cross-countries studies also conclude on a reciprocal effect [9,10]. In short, while the empirical literature is conclusive on the linkages between financial development and economic growth, there is little evidence on the direction of causality.…”
Section: Introductionmentioning
confidence: 99%
“…The findings showed that financial development has a negative effect on growth in long-run, according to Yucel (2009), the presence of structural breaks indicate a stable long-run with the negative link, according to Elijah & Hamza (2019) and, in the case of the short run, broad money supply have negative effects on economic growth (Sultana, 2018). Some studies have also found that there is bidirectional causality between financial development and economic growth (Lewis, 1995;Demetriades & Hussein, 1996;Baliamoune-Lutz, 2013;Murthy, et al, 2014;KAR, et al, 2014;Simionescu, et al, 2017). Trade openness has a positive significant impact on economic growth and the results also show that trade openness is the significant driving force for growth in the long run (Khan & Qayyum, 2007;Yucel, 2009;Shahbaz, 2012;Tsaurai, 2017;Obeid & Awad, 2018;Chandrashekar, et al, 2018;Nwadike, et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 96%
“…Other researchers hypothesise that economic growth causes financial development (Lucas, 1988;Stern, 1989). The empirical findings on the causal relationship between financial sector development and growth have been mixed (Baliamoune-Lutz, 2013;Ewetah and Okodua, 2013;Akinlo and Egbetunde, 2010;Dabos and Gantman, 2010).…”
Section: Theoretical Aspects and Literature Reviewmentioning
confidence: 99%